The contribution of energy use and financial development by source in climate change mitigation process: A global empirical perspective. (1st April 2017) - Riti, Joshua Sunday; Yang Shu,; Deyong Song,; Kamah, Miriam
Abstract: The danger of climate change has over the years become a reality in the public domain. While efforts to mitigate climate change involve energy mix, energy efficiency and cleaner technology, financial development has also been considered as an important factor. Indicator of financial development may draw FDI and advanced degree of research and development which can accelerate economic growth and hence affect dynamism of environmental performance. This study examines the impacts of energy use and financial development indicators by source in the environment-growth-energy model for 90 countries categorized on the basis of income possession over the period 1980–2014. The study applies the panel analysis that accounts for cross-sectional dependence and heterogeneity of series used in the estimation. Results from panel Dynamic Ordinary Least Squares (DOLS) show that in all the categories of countries, fossil fuel energy use and GDP per capita are found to be the major drivers of CO2 emissions though fossil fuel energy use possesses the bigger elasticities. Population however, displays a sign contrary to expectation regarding economic theory in high income countries. Renewable energy and financial development on the other hand are capable of reducing CO2 emissions. However, the magnitude of the long-run elasticity of CO2 emissions with respect to renewable energy use and financial development are much greater in the models with M2 /GDP than the model with M2 /Reserve especially in the high income countries. Policies should be geared towards stimulating investments in renewable energy technology. There is need to develop robust financial systems to lend financial credence to research institutes to work towards producing energy that have less carbon or are carbon-free. Graphical abstract: Highlights: Results support fossil fuel, growth and population rise-emission link. Renewable energy, financial development-carbon emission free. DOLS model with M2/GDP has long-run elasticities of REN and FD than M2/Reserve. FD negatively signed in MIC while insignificant in LIC. Stimulation of investment in renewable energy technology and development of robust financial system.